Risk stratification in patients with heart failure and in patients with implantable cardioverter-defibrillators - Velavan, Periaswamy (2011)
Heart failure is a very common medical condition with significant mortality and morbidity. Patients hospitalised with heart failure are at high risk of death in the short term and patients with chronic heart failure in the community are also at a high risk of death in the medium to long term. It is difficult to accurately identify those at a higher risk of death as current methods of risk stratification lack both sensitivity and specificity. The available treatments for prevention of sudden death in patients with heart failure such as Implantable Cardioverter Defibrillators (ICD) are expensive and do not abolish the risk of sudden death completely. Hence it is necessary to improve risk stratification methods in patients with heart failure and identify factors predicting mortality in those patients with ICD protection. This thesis first describes a series of studies examining the clinical factors that predict increased risk of short-term mortality in patients with a recent hospitalisation for heart failure. These include examination of patient demographics, clinical history and examination, blood tests, electro-cardiographic and echo-cardiographic variables and medication. Based on these variables, I have formulated a simple scoring system to predict short term mortality in hospitalised patients with heart failure. This score was validated in a prospective study of contemporary heart failure population with a recent hospital admission. The relationship of cholesterol and risk of death in heart failure was examined in detail. Then, the utility of Holter monitoring and signal averaged electro cardiograms (SAECG) for risk stratification were examined based on the prognostic value of abnormalities found by these tests in patients with chronic heart failure. Finally patients with heart failure deemed at high risk of sudden death and had ICDs implanted were studied and factors predicting shocks and mortality were identified. Two separate studies were done, first in population who had ICDs mainly for secondary prevention and the second in patient population who had ICDs exclusively for primary prevention. From these studies, I have identified those clinical characteristics that are associated with high risk of death in patients with acute and chronic heart failure and those associated with death in patients with heart failure after ICD implantation.
HydraID: hull:5294 Hydra Discover Access Group: public ETD Collection: ETDPostgraduateMedicalInstitute
Keywords: Medicine